Legal Manoeuvres and Violence: Law Making, Protest and Semi‐Authoritarianism in Uganda. Issue 4 (28th May 2014) - Goodfellow, Tom
ABSTRACT This article explores the interplay between violent protest and the making of laws in Uganda. It advances two main arguments. First, since multipartyism was restored in 2005, the Ugandan government has repeatedly drafted intentionally contentious new laws in part to provoke, divide and politically manipulate opposition. Implementing these laws has often not appeared to be a priority; rather, drafting, debating and (sometimes) passing them represent tactical 'legal manoeuvres' geared towards political gain. Second, I argue that these manoeuvres can be linked to another trend since 2005: the rise in urban‐based protests and riots, which have often become violent and resulted in aggressive crackdowns by the state. In bringing these trends together, this article argues that the use of legislative processes as part of a strategic repertoire to destabilize political opposition has exacerbated unrest, especially among urban dwellers. Moreover, in response to rising protest the government has engaged in further legal manoeuvring. The analysis suggests that the semi‐authoritarian nature of the regime in power, where the symbolic importance of the legislature and relatively free media contend with fundamentally authoritarian tendencies at the centre, is propagating this cycle of legal manoeuvres and violence.